Examining the Therapeutic Processes Associated With Conservative Christian Parental Acceptance of Their Son or Daughter's Lesbian, Gay, or Bisexual Orientation. (July 2018) - Cavallo, Francis J.; Bradley, Christopher
Parents with strong conservative Christian religious beliefs may view their son or daughter's lesbian, gay, or bisexual (LGB) orientation disclosure as a family crisis, and as a result, may seek out support and direction from a Licensed Christian Mental Health Practitioner (LCMHP). The counsel that the LCMHP provides, and a parent's subsequent responses to his or her disclosing son or daughter, can have substantive and enduring positive or negative impacts on the youth's physical and mental health. While it is known that parents can become more accepting of their LGB-oriented son or daughter, the processes by which greater acceptance occurs for conservative Christian parents has yet to be fully examined. The present study employed an interpretative phenomenological analysis research methodology to garner a greater understanding of the conservative Christian parental acceptance phenomena that occurs within the context of a therapeutic engagement between parents and an LCMHP. Providing a greater understanding of the processes and meanings associated with this phenomenon will provide LCMHPs with information that could assist them in helping conservative Christian parents to better navigate their relationship with their LGB-oriented son or daughter.